Effect of a flame-retardant coating on the burning parameters of wood samples - Tsapko, Yu.; Bondarenko, O.; Tsapko, A. (My University, 2019)
Wood is widely used as a building material in construction and architecture due to its mechanical and operational properties. However, because of its high combustibility, it is a fire-hazardous material. Level of fire safety of objects in which wood building structures are used can be raised by means of fire protection treatment, namely, providing the wood with the ability to withstand flame and its surface propagation, preventing free access of oxygen which promotes wood destruction and accelerates the burning process.
Проведеними дослідженнями впливу вогнезахисту дереви- ни на займання встановлено параметри поширення полум’я та пригнічення горіння, що дає можливість впливати на цей процес.
Keywords: захисні засоби; вогнестійкість; втрата маси; оброблення поверхні; швидкість вигорання деревини; ефективність захисту; zasobi; building material; construction; 674.049.3